Next-to-next-to-leading-order QCD corrections to J/ψ plus η c production at the B factories - Xu-Dong Huang; Bin Gong; Jian-Xiong Wang (Journal of High Energy Physics, 2023)
Abstract In this paper, we calculate the next-to-next-to-leading-order (NNLO) QCD corrections to e + e − → J/ψ + η c at the B factories. After including the NNLO corrections, the cross section of e + e − → J/ψ +η c is enhanced by about 17%, and the perturbative series of the prediction shows the convergent behavior. It is also found that the contributions from bottom quark starts at the α s 3 $$ α_s^3 $$ -order, which is about 2.4% of the total prediction. The renormalization scale μ R dependence of the cross section is reduced at the NNLO level, but the prediction is sensitive to the charm quark mass m c . By considering the uncertainties caused by renormalization scale μ R , charm quark mass m c and the NRQCD factorization scale μ Λ, our prediction shows agreement with the BABAR and BELLE measurements within errors.